(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Environmental protection is a top priority, and this can only be accomplished by minimizing Chemicals are used in the manufacturing of fuel. As a biofuel source, bioethanol production waste has become more and more attractive. Using a proper pretreatment technique, it may be transformed into a useful form for biofuel generation. Researchers have employed a variety of pretreatment techniques, including physical, chemical, physicochemical, biological, and combination pretreatments. Because a significant quantity of chemicals are required to pretreat the lignocellulosic substrate, chemical pretreatment is clearly more costly. Combination pretreatments have been proven to be more successful than solo pretreatments, and there is a wide range of combinations that may be used in the future. A recent study critically examines and analyzes various pretreatment techniques, biomass supplies, chemical makeup of various agricultural biomass, and its application for bioenergy production. Various bioHydrogen, bioMethane, bioEthanol, bioMethanol, bioButanol, and bioDiesel pretreatment methods are also addressed.